Mental Health in the Construction Industry - ALsenani, Ibrahim Eid; Aljohani, Abdullah Magboul (Journal of agricultural, environmental and veterinary sciences, 2021)
The study aims to include all work risks, which we will focus on in our study on psychological aspects that have great importance in the success of work and the safety of workers. Therefore, the focus was on the Copenhagen questionnaire Famous Psychosocial. The study followed the descriptive and analytical approach, using the questionnaire is a tool developed and developed by the National Center for Workers Environment (NRCWE) in Denmark with the aim of evaluating and improving the psychological and social work environment, and it consists of three parts: a long questionnaire that uses In research - an intermediate questionnaire used by specialists in the work environment - a short questionnaire used by professionals in the workplace, and it was developed in order to be able to evaluate the practical performance in the psychological and social environment within the field of work. The study concluded that the individuals of the research sample suffer from mental illnesses in a moderate way, and among the most prominent sources of mental illness are the following: sleep disturbances, feelings of tension and worker’s energy consumption, discomfort from important changes and decisions, fear, anxiety, and frustration. The results showed a statistically significant direct relationship between the dimensions of the psychological situation between them, as well as a statistically significant direct relationship between the dimensions of the psychological situation and the overall degree of the dimensions. There were no statistically significant differences at a significance level of 0.05 in the dimensions of the psychological situation according to the variables.